Argument and change in world politics : ethics, decolonization, and humanitarian intervention - Crawford, Neta (Cambridge studies in international relations ;, 2002)
Arguments have consequences in world politics that are as real as the military forces of states or the balance of power among them. Neta Crawford shows how ethical arguments, not power politics or economics, explain decolonization, the biggest change in world politics over the last five hundred years.